BS EN 62841-3-10 AMD AB. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 3-10. Particular requirements for transportable cut-off machines (29th January 2021) - British Standards Institution,
No abstract available